Mental well-being among COVID-19 patients in isolation house - Rini Mustikasari Kurnia Pratama; Diane Marlin; Silvia Mariana (Intelektual Pustaka Media Utama, 2023)
Psychosocial effects of COVID-19 patients have a long-term impact. Isolation is carried out to prevent transmission of the virus for several months causing anxiety, saturation, and even patients experiencing insomnia. Well-being is very subjective, differing from one individual to another, and where well-being can be used as an indicator of a person's happiness or not. The sample this study was amounted to 50 people who were COVID-19 patients. They were undergoing self-isolation in the isolation house of Jambi Province, Indonesia. The study was conducted using self report questionarre 29 (SRQ 29) and subjective well-being scale. In this study, most of the respondents experienced mental emotionaldisorders, negative emotions, and felt satisfied in living their lives. They experienced insomnia or sleep disorders.